Phase transition from a d(x(2)-y(2)) to d(x(2)-y(2))+id(xy) superconductor - Ghosh, A.; Adhikari, S. K. (Elsevier B.V., 1998)
The temperature dependencies of specific heat and spin susceptibility of a coupled d(x2-y2) + id(xy) superconductor in the presence of a weak d(xy) component are investigated in the tight-binding model (1) on square lattice and (2) on a lattice with orthorhombic distortion. As the temperature is lowered past the critical temperature T-c, first a less ordered d(x2-y2) superconductor is created, which changes to a more ordered d(x2-y2) + id(xy) superconductor at T-c1(< T-c). This manifests in two second order phase transitions identified by two jumps in specific heat at T-c and T-c1. The temperature dependencies of the superconducting observables exhibit a change from power-law to exponential behavior as temperature is lowered below T-c1 and confirm the new phase transition. (C) 1998 Published by Elsevier B.V. B.V. All rights reserved.
Keywords: d(x(2)-y(2))+id(xy)-wave superconductor; specific heat; susceptibility